Lactobacillus paracasei Supplementation Prevents Early Life Stress-Induced Anxiety and Depressive-Like Behavior in Maternal Separation Model-Possible Involvement of Microbiota-Gut-Brain Axis in Differential Regulation of MicroRNA124a/132 and Glutamate Receptors - Karen, Christopher; Shyu, Douglas J. H.; Rajan, Koilmani Emmanuvel (Frontiers in Neuroscience, 2021)
This study was designed to investigate the early-life stressful social experience (SSE) induced alteration in microbiota-gut-brain axis. To test this, experimental groups [maternally separated pups (MS) were allowed to experience the presence of a stranger (S) either with mother (M+P+S) or without their mother (MS+S-M). Animals were assessed for anxiety-like behaviour and high-throughput bacterial 16s rRNA sequencing was performed to analyse the gut microbiota structure. Our analysis revealed that early-life SSE induced anxiety-like behaviour, reduced the diversity and richness of gut microbiota. In the second experiment, all the groups were supplemented with Lactobacillus paracasei HT6. Supplementation of Lactobacillus had significant beneficial effect on anxiety-like behaviour in stressed (MS, M+P+S and MS+S-M) rats accompanied with the normalised levels of adrenocorticotropic hormone (ACTH), corticosterone (CORT), glucocorticoid receptor (GR), serotonin (5-HT), dopamine (DA) and noradrenaline (NA). Concomitantly, the expression of microRNA (miR)-124a was down-regulated and microRNA-132, caspase-3, glutamate receptors (GluR1, GluR 2; NR2A, NR2B) were up-regulated in stressed groups but remained unchanged by Lactobacillus supplementation in stressed individuals. In correspondence, stress associated GluR1-GR altered interactions that are significantly prevented by supplementation of Lactobacillus. Finally, fecal metabolite profile analysis revealed that five predicted microbial neuroactive metabolites were reduced by early-life SSE, where effect of Lactobacillus was analyzed. Our results showed a potential link between supplementation of Lactobacillus and beneficial effects on anxiety-like behaviour, which mechanism could be potentially mediated through stress hormones, neurotransmitter, and expression of microRNAmiRNAs, glutamate receptors and microbiota-gut-brain axis.